Beliefs About Dysmenorrhea and Their Relationship to Self‐Management. Issue 4 (13th May 2016) - Chen, Chen X.; Kwekkeboom, Kristine L.; Ward, Sandra E.
Abstract: Dysmenorrhea is highly prevalent and is the leading cause of work and school absences among women of reproductive age. However, self‐management of dysmenorrhea is not well understood in the US, and little evidence is available on factors that influence dysmenorrhea self‐management. Guided by the Common Sense Model, we examined women's representations of dysmenorrhea (beliefs about causes, symptoms, consequences, timeline, controllability, coherence, and emotional responses), described their dysmenorrhea self‐management behaviors, and investigated the relationship between representations and self‐management behaviors. We conducted a cross‐sectional, web‐based survey of 762 adult women who had dysmenorrhea symptoms in the last six months. Participants had varied beliefs about the causes of their dysmenorrhea symptoms, which were perceived as a normal part of life. Dysmenorrhea symptoms were reported as moderately severe, with consequences that moderately affected daily life. Women believed they understood their symptoms moderately well and perceived them as moderately controllable but them to continue through menopause. Most women did not seek professional care but rather used a variety of pharmacologic and complementary health approaches. Care‐seeking and use of self‐management strategies were associated with common sense beliefs about dysmenorrhea cause, consequences, timeline, and controllability. The findings may inform development and testing of self‐management interventions that address dysmenorrhea representations and facilitate evidence‐based management. © 2016 Wiley Periodicals, Inc.